Osteometry of Lumbar Vertebrae of Asiatic Lion (Panthera leo) - Pandey, Sweta; Suman, Alka; Bhyani, DM (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The anatomy of lumbar vertebrae of Asiatic lion was studied. There were seven lumbar vertebrae. The length of the body increased from the first to the sixth vertebrae, whereas the width increased up to the last vertebra. The ventral ridge was absent in first and last vertebrae. The dorsal spinous processes were short and flattened laterally and were cranially inclined, except L7 which was vertical. The transverse processes of each lumbar vertebra were directed obliquely forward and downward. The length of accessory processes decreased from L1 to L6 and it was absent in L7.
Keywords: Lion; Lumbar; Vertebrae; Spine; Process; Biometry